Solution for Distributed Model of Groundwater System with PCG2 for Naolihe Basin in Sanjiang Plain - GUO Longzhu WANG Fulin PENG Shengmin (The journal of Northeast Agricultural University, 2009)
PCG2 （Preconditioned Conjugate-Gradient Method 2）, the most popular mothod used in groundwater field, was used to solve the distributed model of large-scale groundwater system. Its principle and effect was analyzed mathematically, and verified by some specific examples. Numerical results acquired by PCG2 are accurate, it demonstrates that PCG2 is effective on methodology itself and man-ralated operation. So PCG2 is worthy of popularizing in the area of groundwater system for numerical analysis.